Ultra‐performance liquid chromatography/multiple reaction monitoring mass spectrometry quantification of trastuzumab in human serum by selective monitoring of a specific peptide marker from the antibody complementarity‐determining regions. (18th June 2017) - Russo, R.; Rega, C.; Caporale, A.; Tonon, G.; Scaramuzza, S.; Selis, F.; Ruvo, M.; Chambery, A.
Abstract : Rationale: Because of the large molecular weight, the structural complexity and the similarity with endogenous immunoglobulins present in high concentrations, in vivo quantitative studies with therapeutic monoclonal antibodies are particularly challenging. In this work, an UPLC/MRM MS‐based methodology is described for the quantification of trastuzumab in human serum by monitoring a novel specific peptide marker located within its heavy chain Complementarity‐Determining Region (CDR). Methods: For maximum sensitivity and selectivity, specific transitions of this diagnostic proteotypic peptide were optimized and monitored at m/z 364.1 → 437.3 (quantitation ion) and m/z 364.1 → 358.0 (confirmation ion). As a proof‐of‐concept, the methodology was applied to the determination of trastuzumab in human serum over a clinically relevant range from 0.02 to 200 μg/mL. The methodology has been evaluated in terms of specificity, linearity, accuracy, precision, detection and quantitation limits. Results: An excellent linear response has been obtained in the range from 0.036 to 3.6 fmol/μL for the standard peptide and from 0.03 to 285 fmol/μL for the trastuzumab in human serum with typical R 2 values of 0.99. The limit of detection (LOD) and limit of quantification (LOQ) are 0.005 fmol/μL and 0.05 fmol/μL, respectively, with mean bias and RSD values of 18% and 1%, respectively, for quality control samples. Conclusions: The strategy used to set up the UPLC/MRM MS methodology based on monitoring specific peptide markers within CDRs can be potentially applied to the detection and quantification of other humanized or human mAbs in biological fluids. Copyright © 2017 John Wiley & Sons, Ltd.